Desenvolvimento de métodos analíticos verdes empregando entalpimetria no infravermelho - Alessio, keiti Oliveira (2018)
Several analytical methods used for quality control of food and pharmaceutical products are based on titrations. Generally, these methods require high amount of reagents leading to the generation of residues. Other drawbacks of titration methods are related to the low throughput and problems on the determination of the reaction end point. A new approach has been proposed in this study, using thermal infrared thermography (TIE) to perform simple and fast analysis including the reduction or substitution of toxic reagents for non toxic ones obtained from renewable sources. Firstly, an equipment was developed using an infrared pyrometer to perform thermometric titration. The optimization of parameters, such as the total volume of solution, sensor distance from the solution and titrant flow rate were performed. Neutralization, redox and complexation reactions were performed and the results were compared with those from official compendia (Brazilian Pharmacopeia and Adolfo Lutz Institute). Therefore, the determination of acidity of sauces, ascorbic acid and calcium content in pharmaceutical products was carried out. The proposed method presented good agreement with official methods ranging from 97 to 104% for all samples, allowing the reduction of the volume of reagents and the generation of residues in agreement to the principles of green analytical chemistry. Additionary, a combination of TIE with microplate paper as reactor it was also proposed. Potato juice was used as reagent for the determination of hydrogen peroxide in pharmaceutical products, bleaching and mouthwash solutions. The experimental parameters as pH of solutions, stability and proportion of reagents were evaluated to ensure the optima experimental conditions. The results were promising reaching good agreement (96 to 103%) with conventional methods for all evaluated samples with official methods (USP and ASTM D2180). Therefore, both methods proposed in this work presented excellent performance, showing to be a suitable alternative for application in routine analysis. Low cost, high throughput and simplicity could be pointed out as features of these methods, which were in agreement to the green analytical chemistry principles.